Seasonal Training Load Monitoring Among Elite Level Soccer Players: Perceived Exertion and Creatine Kinase Variations Between Microcycles - Mendes, B.; Clemente, F. M.; Calvete, F.; Carriço, S.; Owen, A. (Journal of Human Kinetics, 2022)
The primary aim of the investigation was to determine the daily load variations between the microcycles of an entire season of an elite group of professional soccer players. The second aim of this study was to determine the relationships between Foster`s rating of perceived exertion (RPE), the Hooper index (HI) and CK levels over the weekly microcycles of the season. Thirty-five male professional soccer players participated in this study (3 goalkeepers, 6 wide defenders, 4 central defenders, 9 midfielders, 8 wide midfielders and 4 forwards) (25.7 ± 5.0 years, 182.3 ± 6.4 cm; 79.1 ± 7.0 kg). Significant differences between months in the variables of HI (p = 0.001; ES = 0.052), minT (p = 0.001; ES = 0.066), IL (p = 0.001; ES = 0.052, minimum effect) and CK (p = 0.002; ES = 0.031) were found. Comparison of the HI (p = 0.044; ES = 0.002), minT (p = 0.001; ES = 0.045), and IL (p = 0.001; ES = 0.045) revealed significant differences between microcycles. No significant differences were found in CK (p = 0.710; ES = 0.001) across the period. A significantly higher internal training load and fatigue perception in microcycles with only one official match was found. The greater load occurred 3 to 4 days before the game. In addition, it can be concluded that the first quarter of the season seemed to induce a greater physical demand on elite professional players.